Violence in Islamic thought from the Mongols to European imperialism - Gleave, R. (Robert); Kristó Nagy, István, 1974- (Legitimate and illegitimate violence in Islamic thought, 2018)
This book examines how violent acts were assessed by Muslim intellectuals, analysing both changes and continuity within Islamic thought over time.